2014
DOI: 10.1109/tmi.2013.2297278
|View full text |Cite
|
Sign up to set email alerts
|

200 MeV Proton Radiography Studies With a Hand Phantom Using a Prototype Proton CT Scanner

Abstract: Proton radiography has applications in patient alignment and verification procedures for proton beam radiation therapy. In this paper, we report an experiment which used 200 MeV protons to generate proton energy-loss and scattering radiographs of a hand phantom. The experiment used the first-generation proton CT scanner prototype, which was installed on the research beam line of the clinical proton synchrotron at Loma Linda University Medical Center (LLUMC). It was found that while both radiographs displayed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…This has been pointed out e.g. by Plautz et al (2014). The true limiting factor in scattering proton CT, however, is the higher image noise so that SNR and CNR turn out to be less favourable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This has been pointed out e.g. by Plautz et al (2014). The true limiting factor in scattering proton CT, however, is the higher image noise so that SNR and CNR turn out to be less favourable.…”
Section: Discussionmentioning
confidence: 97%
“…An appealing practical aspect of scattering proton CT is that the imaging system is simpler than in energy-loss proton CT: it only requires tracking devices (to measure a proton's direction upstream and downstream of the object), but no detector to measure a proton's residual energy. It has also been observed that scattering proton CT might provide higher contrast images than energy-loss proton CT (Plautz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is appropriate to note that imaging using the angular deflection of protons has been proposed before and planar images of median scattering-angle have been demonstrated experimentally. 22 Tomographic reconstructions of inverse scattering length (closely related to absolute scattering-power) have been demonstrated in simulation. 23,24 Further, we note that nuclear scattering tomography (NST) with protons has long been established, but this relies on very different principles (wide-angle single scattering).…”
Section: Discussionmentioning
confidence: 99%
“…This modality would definitely improve with a clinical use of proton radiography, which provides direct information on the density of the tissues, enhancing the precision of treatment planning. In this framework, different proton radiography systems have been tested [1][2][3]. Our group investigated the possibility of using emulsion detectors [4] to image different phantoms of the proton therapeutic beam at the Paul Scherrer Institut (PSI) in Villigen, Switzerland.…”
Section: Introductionmentioning
confidence: 99%